Euro-Area Banking At the Crossroads - Belaisch, Agnes (IMF Working Papers; Working Paper ;, 2001)
This paper analyses the process of disintermediation, the progress in consolidation, the impact of new technologies, and the role of ownership and control structures for the euro area banking sector. The impact of these trends on competition policy, "too big to fail" concerns, and financial stability is investigated. In this setting, the paper endorses stronger cross-border coordination among supervisory authorities but notes that more formal cross-border arrangements through supranational agencies seem, at this stage, premature. However, an increased capacity to perform centralized market surveillance, building on domestic supervisory information, is needed to ensure the efficiency and stability of euro-area financial markets.